2019
DOI: 10.1109/tsg.2017.2752712
|View full text |Cite
|
Sign up to set email alerts
|

Generic Demand Model Considering the Impact of Prosumers for Future Grid Scenario Analysis

Abstract: The increasing uptake of residential PV-battery systems is bound to significantly change demand patterns of future power systems and, consequently, their dynamic performance. In this paper, we propose a generic demand model that captures the aggregated effect of a large population of price-responsive users equipped with small-scale PV-battery systems, called prosumers, for market simulation in future grid scenario analysis. The model is formulated as a bi-level program in which the upper-level unit commitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…The opportunities offered by demand side resources have also been recognized by the Australian Energy Market Commission [197], who argue that consumers with PV-battery systems can provide network support and ancillary services that were traditionally confined to the domain of large generators. Indeed, [198], [199] showed that a high penetration of prosumers, consumers equipped with rooftop solar and battery storage, changes the demand profile in ways that significantly improve the system loadability [198] and frequency performance [199].…”
Section: Distributed Controlmentioning
confidence: 99%
“…The opportunities offered by demand side resources have also been recognized by the Australian Energy Market Commission [197], who argue that consumers with PV-battery systems can provide network support and ancillary services that were traditionally confined to the domain of large generators. Indeed, [198], [199] showed that a high penetration of prosumers, consumers equipped with rooftop solar and battery storage, changes the demand profile in ways that significantly improve the system loadability [198] and frequency performance [199].…”
Section: Distributed Controlmentioning
confidence: 99%
“…Nonetheless, significant benefits can be derived through proper management The authors gratefully acknowledge the partial support for this research received from the Victorian Governments veski programme. and control of DER as they have the potential to assume a central role in the future grid stability and security [5]. Recently, in the Open Energy Network (OEN) consultation paper [6], Energy Network Australia and the Australian Electricity Market Operator expressed the need and urgency to integrate DER and tap their flexibility potential in order to reduce electricity costs.…”
Section: Introductionmentioning
confidence: 99%
“…In this problem, (24) stands for the load balance of the prosumers; the charging and discharging of ESSs is presented in (25); PV modules to be installed at hour t are defined in (26)- (27), (28) stands for the maximum investment cost at hour t; charging and discharging limits of ESSs of the ICES are presented in (29)-(30), respectively; the maximum contracted power that a prosumer can buy from the ICES is stated in (31); (32) shows that the price of electricity that a prosumer may sell to the ICES should remain lower than a price threshold proportional to the price of electricity that it buys from market; (33) stands for the energy, via a predefined contract, that a prosumer can buy from the WM; (34), (35), and (36) represent investment, generation, and maintenance costs of the PV units of the prosumers; and (37) stands for the charging and discharging costs of ESSs.…”
Section: B Lower Levelmentioning
confidence: 99%
“…A comprehensive literature review on siting and sizing of DG units was presented in [25], while, in [26], a bilevel DR-based planning framework for distribution network and renewable energy expansion was shown. In [27], aiming at addressing the future grid issues, a bilevel program in which the upper-level minimizes the total generation cost, and the lower-level maximizes the prosumers' aggregate self-consumption while no interaction between the WM and the aggregator was considered. In [6], flexibility in power systems planning in the presence of flexible resources such as conventional units, ESSs, heat storage devices, and electric boilers was studied.…”
Section: Introductionmentioning
confidence: 99%